From Loss to Loneliness: The Effects of Prolonged Grief in Elderly - Julia Dian Christiani Adi Santoso; Hendy Muagiri (Jurnal Psikiatri Surabaya, 2024)
Introduction: COVID-19 high death tolls have brought about many bereavements all over the world. In this brief report, we aim to describe the effects of traumatic end-of-life experiences causing prolonged grief and loneliness as mediators for psychiatric disorders in the elderly. Case: The patient was a 60-year-old woman with chronic sleep disturbance since her only daughter suddenly passed away after several days of being isolated in the hospital during the COVID-19 pandemic and being hastily buried with the COVID-19 protocols. The patient yearned for her daughter but at the same time also avoided all memories of her daughter. She felt anxious most of the day which escalated to panic attacks requiring visits to the emergency room. Various examinations were carried out with normal results, except for blood pressure. She was diagnosed with prolonged grief, generalized anxiety, post-traumatic stress disorder, and hypertension. Treatments included SSRI, benzodiazepine, antihypertensive medicine, and psychotherapy. Improvements were significant within 9 months of therapy. Discussion: Traumatic end-of-life events may precipitate prolonged grief and loneliness. Bereavement is the most common cause of loneliness in the elderly. Untreated prolonged grief and loneliness generate a loss of sense of self and purpose and are associated with low-grade peripheral inflammation and poor health. The combination of pharmacotherapy and psychotherapy is the most effective treatment which improves the patient’s outcome significantly. Conclusion: Traumatic end-of-life experiences are associated with prolonged grief disorder, poor physical and mental health outcomes, hence the right holistic approach is necessary to improve patient outcomes. Keywords: Prolonged Grief, Loneliness